Live fast, die young: Behavioural and physiological impacts of light pollution on a marine fish during larval recruitment. (September 2019) - O'Connor, J.J.; Fobert, E.K.; Besson, M.; Jacob, H.; Lecchini, D.
Abstract: Artificial light at night (ALAN) is a recently acknowledged form of anthropogenic pollution of growing concern to the biology and ecology of exposed organisms. Though ALAN can have detrimental effects on physiology and behaviour, we have little understanding of how marine organisms in coastal areas may be impacted. Here, we investigated the effects of ALAN exposure on coral reef fish larvae during the critical recruitment stage, encompassing settlement, metamorphosis, and post-settlement survival. We found that larvae avoided illuminated settlement habitats, however those living under ALAN conditions for 10 days post-settlement experienced changes in swimming behaviour and higher susceptibility to nocturnal predation. Although ALAN-exposed fish grew faster and heavier than control fish, they also experienced significantly higher mortality rates by the end of the experimental period. This is the first study on the ecological impacts of ALAN during the early life history of marine fish. Graphical abstract: Exposure of fish to artificial light at night during the recruitment stage. Results show various behavioural and physiological impacts of light pollution including habitat avoidance at settlement (A.), disruption to endocrine and metabolic systems during metamorphosis (B.) and increased susceptibility to predation as post-larvae (C.). Unlabelled Image